The spin-correlated radical pair as a reaction intermediate - McLauchlan, Keith A.; Steiner, Ulrich (My University, 1991)
The concept of the spin-correlated radical pair has been used for some time in the interpretation of the results of magnetic polarization experiments in NMR and in ESR (CIDNP and CIDEP), and of the effects of magnetic fields on chemical reactions. It has, however, a much wider general significance as a reaction intermediate in all radical reactions, including photochemistry. Here the nature of the pair is introduced, and the evidence for it reviewed, and it is further shown how it can be treated theoretically, before some of the consequences of its existence are pointed out. Its recognition, and in particular the understanding of the processes which occur within it, notably the interplay of spin-mixing and diffusion, allow the design of new experiments in the absence or presence of an external magnetic field, and the optimization of reaction yields.
Keywords: 540